Oculo–facio–cardio–dental syndrome with craniosynostosis, temporal hypertrichosis, and deafness. Issue 5 (20th March 2017) - O'Byrne, James J.; Laffan, Eoghan; Murray, Dylan J.; Reardon, William
Abstract : We report the case of a 7‐month‐old girl with atypical oculo–facio–cardio–dental syndrome (OFCD). A novel de novo pathogenic mutation in the BCL6 interacting co‐repressor gene ( BCOR ) (c.4540C>T; p.Arg1514*), was identified on the X chromosome. This case expands the phenotype of OFCD as it is the first report of a case presenting with craniosynostois, temporal hypertrichosis, supraorbital grooving, and underdevelopment of the midface.